Ten Points for Urban Play: a Multidisciplinary Approach - Mattia Thibault; Valerio Perna; Antonio Opromolla (Interaction Design and Architecture(s))
The importance of playfulness in the creation of cohesive and sustainable urban communities is being increasingly recognised not only in urban studies but also in other disciplines such as human-centered design, architecture and semiotics, which are devoting an increasing number of studies to the potential, the creation and the effects of various forms of playful interactions with urban spaces. This convergence of interests makes it urgent to find common concepts leading to a holistic understanding of the phenomenon. In this paper, authors with different backgrounds (semiotics, architecture and design) but with a common interest in urban playfulness initiate a multidisciplinary dialogue. Such dialogue was articulated in five phases – Exploration, Integration, Categorisation, Selection and Description – and produced a total of ten strong concepts. This list offers a platform for the understanding, study, and design of urban playfulness.